The heat is on - Harper, Charise Mericle (Harper, Charise Mericle. Next best junior chef, 2018)
The second week of Next Best Junior Chef features family and traditions, as Caroline, Oliver, and Rae, ages eleven to twelve, face more challenges and another elimination.